High piezocatalytic performance driven by peak flow kinetic energy in polymer piezoelectric composite films - Wenpeng Gao; Bing Xie; Zhiyong Liu; Kun Guo; Pu Mao (Journal of Advanced Dielectrics)
Piezocatalysis is an emerging approach for degrading organic dye. However, the limited availability of ultrasonic resources in nature restricts its practical application. Our proposed peak flow kinetic energy piezocatalytic strategy, based on a “waterfall flow” model, aims to simulate the piezocatalytic degradation of pollutants in nature. This innovative strategy can enhance degradation efficiency by adjusting the flow rate and drop height. When 140[Formula: see text]mL of rhodamine B (RhB) dye solution flows at a rate of 1000[Formula: see text]mL/min from a height of 48[Formula: see text]cm and impacts a 3 cm diameter BaTiO3 nanowires/PVDF piezoelectric composite film, a degradation rate of 90% can be achieved within 120[Formula: see text]min. This rapid degradation is primarily attributed to the efficient conversion of kinetic energy into impact force as the water falls, which triggers the generation of piezopotential in the composite film. This, in turn, drives the separation and transmission of electron–hole pairs, leading to the promotion of reactive oxygen species (ROS) generation and facilitating fast organic dye degradation. The pulsating nature of the impact force ensures a continuous generation of ROS. This approach is poised to advance piezocatalysis for the degradation of organic dyes in natural environments and presents a novel method for wastewater treatment.